Challenges for the 21st century. - McKinley, Brunson; Von Koppenfels, Amanda Klekowski; Laczko, Frank (Forum for Applied Research & Public Policy)
International migration is a global issue that needs international cooperation among states. According to the International Organization for Migration, migration at the beginning of the 21st century is at an all-time high level, with over 150 million migrants documented and many more illegal. Given the global scale of the issue, it is only through international multilateral cooperation that the benefits of international migration can be taken advantage of and the welfare of migrants ensured.